Evaluation and SNP typing of DNA from ultraviolet-irradiated human bloodstains using TaqMan assay - Jian Tie (Nature Portfolio, 2021)
Abstract When detecting DNA profiles from forensic materials, it is pivotal to know the extent of degradation and which DNA marker can be genotyped. Ultraviolet (UV) is one of the common external factors that causes DNA damage, through which, an attempt to reveal cardinal genetic information can be made. In this study, after irradiation with three different UV wavelengths, UV-damaged DNA in the bloodstains was analyzed with long and short TaqMan assays using real-time PCR. In addition, both short tandem repeat (STR) profiles and single nucleotide polymorphisms (SNPs) from the damaged DNA at different stages of UV exposure were also assessed. With increasing in UV irradiation cycles, there was a delay of the amplification curves accompanied with a decrease in the DNA amounts collected. Despite the amplification of STR genotype was not altered after 75 cycles of UVC irradiation, all 12 SNP loci could still be detected. Furthermore, a short-assay line was detected in the absence of an amplification of the evaluation curve. The results indicate that, although the DNA template might not be useful and suitable for analysis of STR profile, this approach is of some values in detecting SNPs.